A Numerical Study of Liquid Sloshing in a Two-dimensional Tank under External Excitations - Hou, Ling; Li, Fangcheng; Wu, Chunliang (Journal of marine science and application, 2012)
In this research, liquid sloshing behavior in a 2-D rectangular tank was simulated using ANSYS-FLUENT software subject to single or multiple-coupled external excitations （such as sway coupled with roll, and sway and roll coupled with heave）. The volume of fluid （VOF） method was used to track the free surface of sloshing. External excitation was imposed through the motion of the tank by using the dynamic mesh technique. The study shows that if the tank is subjected to multiple coupled excitations and resonant excitation frequencies, liquid sloshing will become violent and sloshing loads, including impact on the top wall, will be intensified.